Intracranial Lesion Detection and Artifact Characterization: Comparative Study of Susceptibility and T2*-Weighted Imaging in Dogs and Cats - Wolfer, Nadja; Wang-Leandro, Adriano; Beckmann, Katrin M.; Richter, Henning; Dennler, Matthias (Frontiers in Veterinary Science, 2021)
Susceptibility-weighted imaging (SWI), an MRI sequence for the detection of hemorrhage, allows differentiation of paramagnetic and diamagnetic substances based on tissue magnetic susceptibility differences. The three aims of this retrospective study included comparison of the quantity of areas of signal void (ASV) between SWI and T2*-weighted imaging (T2*WI), differentiation of hemorrhage and calcification, and investigation of image deterioration by artifacts. Two hundred and twelve brain MRI, 160 dogs and 52 cats, were included. The sequences were randomized and evaluated for presence/absence and numbers of ASV and extent of artifacts causing image deterioration by a single, blinded observer. In cases with a CT scan differentiation of paramagnetic (hemorrhagic) and diamagnetic (calcification) lesions was made in SWI to test correct assignment using the Hounsfield Units. Non-parametric tests were performed to compare both sequences regarding detection of ASV and the effect of artifacts on image quality. Presence of ASV was found in 37 SWI sequences and 34 T2*WI sequences with a significant increase in ASV only in dogs > 5 and ≤ 15 kg in SWI. The remaining weight categories showed no significance. CT examination was available in 11 cases in which 81 ASV were found. Using phase images, 77 were classified as paramagnetic, none as diamagnetic. Classification was not possible in 4 cases. At the level of the frontal sinus, significantly more severe artifacts occurred in cats and dogs (dogs: p  0.001; cats: p = 0.001) in SWI. The frontal sinus artifact was significantly less severe in brachycephalic than in non-brachycephalic dogs in both sequences (SWI: p= < 0.001; T2*WI: p= < 0.001). In conclusion, the advantages of better detection of ASV in SWI compared to T2*WI and the opportunity to differentiate between paramagnetic and diamagnetic origin in most cases, SWI is generally recommended for dogs. Frontal sinus conformation appears to be a limiting factor in image interpretation.